Anxiety and depression among cancer patients in Ethiopia: a systematic review and meta-analysis - Geremew, Habtamu; Abdisa, Samuel; Mazengia, Elyas Melaku; Tilahun, Werkneh Melkie; Haimanot, Aysheshim Belaineh; Tesfie, Tigabu Kidie; Mneneh, Anteneh Lamesgen; Mengie, Muluye Gebrie; Endalew, Bekalu; Birhanu, Molla Yigzaw; Asmare, Lakew; Simegn, Mulat Belay (Frontiers in Psychiatry, 2024)
Introduction: Anxiety and depression are among the common comorbidities of people diagnosed with cancer. However, despite the progress in therapeutic options and outcomes, mental health care and support have lagged behind for cancer patients. Estimating the extent and determinants of mental health disorders among cancer patients is crucial to alert concerned bodies for action. In view of this, we aimed to determine the pooled prevalence and determinants of anxiety and depression among cancer patients in Ethiopia.